Youth Unemployment and Participation in Political Violence in EyeCourt, Harare - Rusike, Vincent Tafara; Mutukwa, Maxwell Tawanda (Advances in Social Sciences Research Journal, 2025)
The main objective of the study was to assess how youth unemployment stimulates youth participation in political violence in Eyecourt and develop a comprehensive understanding of other unemployment interrelated factors and their interrelationships in driving political violence among youths in the area. Using a qualitative research methodology, the study utilized Eyecourt Township as a case study. Thirty participants, both perpetrators and victims of political violence, were selected using snowball sampling. Data collection tools included in-depth interviews and focus group discussions and were analyzed using thematic analysis. The study found that youth unemployment significantly drives political violence. Other related factors such as limited economic opportunities; lack of civic education fosters intolerance and violent behavior towards political opponents; political terrain in Zimbabwe, stimulates youth involvement in political violence; and rapid urbanization exacerbates the situation by creating large pools of idle youths susceptible to recruitment for militias and contestations for land. The study concludes that these are key factors explaining youth participation in political violence. It recommends targeted interventions such as conflict early warning systems, special youth economic zones, vocational training, and the establishment of special courts to handle political violence cases. These measures aim to create economic opportunities, reduce youth frustration and aggression, fostering stability and peace in Harare and across Zimbabwe.